Casting and Forming of Advanced Aluminum Alloys - Puga, Hélder (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint provides a comprehensive exploration of cutting-edge developments in aluminum alloy casting and forming processes. Comprising a collection of articles, it delves into the diverse processing techniques, metallurgical complexities, and mechanical characteristics of these extraordinary materials. Each contribution serves as a catalyst for progress in advanced aluminum alloy applications, meticulously addressing challenges and offering innovative solutions.